Significance of communication during the outbreak of pandemic towards communities: a comparative study Covid-19 and Spanish Flu (H1N1) / Wardatul Hayat Adnan, Khairi Khairuddin And Ahlam Abdul Aziz - Adnan, Wardatul Hayat; Khairuddin, Khairi; Abdul Aziz, Ahlam (Centre For Media And Information Warfare Studies, 2021)
Significance of communication during the outbreak of pandemic towards communities: a comparative study Covid-19 and Spanish Flu (H1N1) / Wardatul Hayat Adnan, Khairi Khairuddin And Ahlam Abdul Aziz Pandemic has caused many of the communities affected in their daily lives. This is not limit to only the ways of doing things but also in a form of communication. It forces communities specifically to response different ways to suit the current environment. Traditionally, in the context of education, classes were conducted in physical face-to-face and presently it was conducted virtually. Due to this, many are struggling to adopt with the new norms practiced among the community. Many sectors are also affected in ways of communication to perform daily tasks. Thus, the present study highlighted a reviews of literature studies based on secondary data to seek further significance of communication during the attach of pandemic comparing from present and previous studies. The two pandemic comparisons made was between Spanish Flu in 1918 also known as H1N1 flu pandemic which killed an estimated 50 million people worldwide, including an estimated 675,000 people in the United States. Meanwhile, the current pandemic namely Covid-19, another stronger virus that has killed 2,682,258 worldwide as at 17 th March 2021. Understanding its significance changing the ways of communities communicating with the limitation due to virus will help researcher as well as readers to understand the importance of adopting the present communication in ensuring the relevancy of communication in the era of 21 st century with the involvement of pandemic situations.